Effects of a 16-week, home-based, high-intensity, progressive resistance training program on glucose homeostasis, cardiovascular disease risk factors and functional capacity of older Malaysians with type 2 diabetes mellitus - Mat Ludin, Arimi Fitri (2013)
Ageing is an inevitable process and it is associated with multiple chronic diseases,one of which is Type 2 Diabetes Mellitus (T2DM). An increasing ageing population in Malaysia means that medical problems which affect the elderly are on the rise. Research has proven that aerobic exercise improves glucose homeostasis. However,the dose and setting in which tests were applied in current research are not viable for implementation on the elderly especially within the general population. Homebased Progressive Resistance Training (PRT) could be an alternative solution, as it promotes favourable improvement on the conditions of the elderly with T2DM. The hypothesis of this study which was a 16-week home-based PRT is associated with a significant improvement on T2DM management among the elderly. In this regard,the aim of this study was to measure the effects of a 16-week home-base high intensity PRT on glucose homeostasis, risk factors and functional capacity among elderly subjects with T2DM. The study also intends to assess the occurrence of adverse events following the exercise protocol. The sample size calculation was done using G-power with Type I and Type II errors set at 5%, effect size f at 0.25. To achieve the predetermined study power, a total of 70 patients, aged 61.7 ± 5.5 years (intervention, n = 35 vs. control, n = 35) attending the Serdang Hospital participated in this quasi-experimental trial. The whole body exercise training regime consisted of 2 main parts: a one-to-one training session for the first two weeks for familiarization and a home-based exercise program for the remaining 14 weeks with monthly follow-ups. Glucose homeostasis (HbA1c and fasting blood glucose level, FBG), body composition (body mass, BMI, fat and muscle mass),cardiovascular risk factors (blood lipid profile, systolic (SBP) and diastolic blood pressures (DBP), resting heart rate, and ankle-brachial index and functional capacity (Sit-to-Stand Test, Stair Climb Test, 6-Minute Walking Test (6MWT), static balance and muscle strength) were measured before and after intervention. With the exception of systolic blood pressure (p < .05), the results revealed no significant difference between intervention and control groups in all variables observed at the baseline prior to commencement of training. The post-intervention measurements showed significant reduction in HbA1c (14.3%, p < .001), FBG (14.1%, p < .001),body mass (0.8%, p < .05), body fat mass (0.9%, p < .05) and systolic blood pressure (1.1%, p < .05). There were significant improvements in functional capacity, i.e. Sitto-Stand (15.2%, p < .001), Stair Climb (11.4%, p < .001) and 6MWT (9.1%, p < .001). Muscle strength also improved significantly, i.e. hand grip strength (7.2%, p < .01),upper body strength (34.0%, p < .05) and lower body strength (48.3%, p < .05). No significant improvements were observed in diastolic blood pressure, heart rate,BMI, lipid profile, static balance and ankle brachial index. There were no significant complications or adverse events reported. This study suggests the exercise regime implemented is effective and caused no adverse events in improving glycemic control, and the functional capacity among the Malaysian elderly with T2DM.